The Effect of Self-Regulated Learning on Academic Procrastination in Hafidz Qur'an Students - Binti Nurhayati (Universitas Muhammadiyah Yogyakarta, 2023)
The purpose of this research is to determine the impact of self- regulated learning on academic procrastination among students memorizing the Quran at PPTQ Al Hamra' Yogyakarta. Ideally, students memorizing the Quran should have self-regulated learning so that the level of academic procrastination is low. However, the reality is that many students who are memorizing the Quran have not been able to provide regulations for themselves, so the level of academic procrastination is high. Survey research employs a quantitative approach. The population of this study was 66 people. Purposive sampling was used, and 40 samples were collected. Data collection techniques use questionnaires and documentation. Data analysis techniques use simple linear regression analysis. The results showed that the determination coefficient value was 66.8%, which means that the influence that self-regulated learning has on the academic procrastination of students in PPTQ Al Hamra' is 66.8%. The value of the regression coefficient is -0.874, which means that the negative self-regulated learning inhibitor of academic procrastination is strong.